Amorphous indium-based catalyst for producing formic acid by reducing carbon dioxide through electro-catalysis and preparation method of amorphous indium-based catalyst

By using amorphous indium-based catalyst prepared by regulating solvent ratio and reaction conditions during the electrocatalytic CO2 reduction process, the problem of poor stability of crystalline catalysts is solved, efficient and stable production of formic acid is achieved, and electrocatalytic CO2 reduction technology is promoted. industrial application.

CN119194491APending Publication Date: 2024-12-27BEIJING FORESTRY UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411375674.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing crystalline indium-based catalysts have problems with low reaction current density and poor stability during the electrocatalytic CO2 reduction formic acid production process, which limits the industrial application of the technology.

Method used

By introducing polyols into the indium oxide (In2O3) catalyst system for thermal synthesis of indium oxide (In2O3) in ethanol solvent, the solvent ratio, reaction temperature and time are adjusted, and amorphous indium-based catalysts are prepared, which significantly improves the activity and stability of the catalyst.

Benefits of technology

It has achieved efficient production of formic acid during electrocatalytic CO2 reduction, and the catalyst maintains high Faraday efficiency and long-term stability at higher current density, which is significantly better than commercial catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194491A_ABST
    Figure CN119194491A_ABST
Patent Text Reader

Abstract

The invention discloses an amorphous indium-based catalyst for producing formic acid through reduction of carbon dioxide under electro-catalysis and a preparation method of the amorphous indium-based catalyst. The amorphous indium-based catalyst is obtained by adopting a solvent regulation and control strategy. A researcher introduces polyhydric alcohol on the basis of an original ethanol solvothermal synthesis indium oxide catalyst system, and synthesis of the catalyst is achieved by regulating and controlling the solvent proportion, the reaction temperature, the reaction time and other elements. The catalyst shows excellent activity and stability in production of formic acid through reduction of carbon dioxide under electro-catalysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electrocatalytic carbon dioxide (CO2) reduction, and in particular relates to an amorphous indium-based catalyst for electrocatalytic CO2 reduction to produce formic acid. Background Art

[0002] With the rapid development of society, human demand for energy is growing. Since the first industrial revolution, the large-scale use of fossil fuels such as coal, oil, and natural gas has led to a large amount of CO2 emissions. The resulting environmental problems such as global warming and seawater acidification have become increasingly prominent, seriously threatening human survival and safety. Therefore, carbon capture, utilization and storage (CCUS) has received more and more attention. Among them, electrocatalytic CO2 reduction technology, as one of the CO2 utilization technologies, can realize the electrochemical conversion of CO2 into high-value-added fuels and chemicals using renewable electricity as energy, and has great development potential. There are many products of electrocatalytic CO2 reduction reaction, among which formic acid can be used as fuel cell raw materials, chemical raw materials, etc., with high economic benefits and broad market prospects.

[0003] Indium-based catalysts are common electrocatalytic CO2 reduction catalysts for producing formic acid. This type of catalyst has the advantages of high formic acid selectivity and low toxicity, but there are still problems such as low reaction current density and poor stability that need to be solved. At present, the most studied indium-based catalysts are crystalline catalysts, which have the problem of poor stability. The characteristics of amorphous catalysts are short-range order and long-range disorder of atoms. Many studies have shown that compared with crystalline catalysts, amorphous catalysts have more randomly oriented unsaturated bonds, more surface exposed defects and abundant low-coordination atoms, which have the advantages of producing more catalytic active sites and showing better activity and stability. Therefore, the development of efficient amorphous indium-based catalysts will be conducive to promoting the industrial application of electrocatalytic CO2 reduction technology for producing formic acid. Summary of the invention

[0004] To solve the above problems, the present invention provides an amorphous indium-based catalyst for electrocatalytic CO2 reduction to produce formic acid and a preparation method thereof, which exhibits excellent activity and stability in electrocatalytic CO2 reduction to produce formic acid.

[0005] The technical solution of the present invention is as follows:

[0006] By adopting a solvent control strategy, polyols were introduced into the original ethanol solvent thermal synthesis of indium oxide (In2O3) catalyst system. By controlling factors such as solvent ratio, reaction temperature, and reaction time, the synthesis of amorphous indium-based (In-amorphous) catalysts was achieved.

[0007] The preparation method of the catalyst comprises the following steps: (1) dissolving 0.002 mol of indium salt in a certain amount of anhydrous ethanol and stirring for about 1 hour until the indium salt is completely dissolved; (2) slowly adding a certain amount of polyol into the solution and continuing stirring for about 1 hour until the solution becomes transparent; (3) transferring the obtained solution into a 100 mL stainless steel autoclave lined with polytetrafluoroethylene and heating it at high temperature for several hours; (4) washing the obtained catalyst by centrifugation or filtration with anhydrous ethanol and water, and finally drying the obtained catalyst in an oven to obtain a powdered amorphous indium-based catalyst.

[0008] In the preparation method, the indium salt in step (1) is indium nitrate and its hydrate, indium chloride and its hydrate, etc.

[0009] In the preparation method, the solvent ratio of polyol to anhydrous ethanol in step (1) and step (2) is 0<polyol:ethanol<1, and the total volume of the mixed solvent is 51 mL.

[0010] In the preparation method, the polyol in step (2) is ethylene glycol, 1,2-propylene glycol, propylene glycol, butanediol (1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol), butanetriol (1,2,3-butanetriol, 1,2,4-butanetriol), butanetetraol, etc.

[0011] In the preparation method, the reaction temperature in step (3) is in the range of 100°C to 200°C.

[0012] In the preparation method, the reaction time in step (3) is in the range of 3 to 10 hours. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 This is the X-ray diffraction analysis (XRD) diagram of the In2O3 catalyst synthesized in Comparative Example 1.

[0014] Figure 2 This is the Faraday efficiency diagram of the electrocatalytic CO2 reduction product of the In2O3 catalyst synthesized in Comparative Example 1.

[0015] Figure 3 This is the Faraday efficiency diagram of the electrocatalytic CO2 reduction product of commercial indium hydroxide (In(OH)3-Commercial) in Comparative Example 2.

[0016] Figure 4 This is a scanning electron microscope (SEM) image of the In-amorphous-1 catalyst synthesized in Example 1 (indium nitrate hydrate, ethylene glycol:ethanol=1:2, reaction temperature 160°C, reaction time 5 hours).

[0017] Figure 5This is an energy dispersive X-ray spectrometer (EDS) graph of the In-amorphous-1 catalyst synthesized in Example 1 (indium nitrate hydrate, ethylene glycol:ethanol=1:2, reaction temperature 160°C, reaction time 5 hours).

[0018] Figure 6 This is a high-magnification transmission electron microscopy (HR-TEM) image of the In-amorphous-1 catalyst synthesized in Example 1 (indium nitrate hydrate, ethylene glycol:ethanol=1:2, reaction temperature 160°C, reaction time 5 hours).

[0019] Figure 7 This is a linear sweep voltammetry test (LSV) graph of the In-amorphous-1 catalyst synthesized in Example 1 (indium nitrate hydrate, ethylene glycol:ethanol=1:2, reaction temperature 160° C., reaction time 5 hours).

[0020] Figure 8 This is a Faraday efficiency diagram of the electrocatalytic CO2 reduction product of the In-amorphous-1 catalyst synthesized in Example 1 (indium nitrate hydrate, ethylene glycol:ethanol=1:2, reaction temperature 160°C, reaction time 5 hours).

[0021] Fig. 9 This is a stability test chart of the electrocatalytic CO2 reduction to produce formic acid of the In-amorphous-1 catalyst synthesized in Example 1 (indium nitrate hydrate, ethylene glycol:ethanol=1:2, reaction temperature 160°C, reaction time 5 hours).

[0022] Fig.10 This is a Faraday efficiency diagram of the electrocatalytic CO2 reduction product of the In-amorphous-2 catalyst synthesized in Example 2 (indium nitrate hydrate, ethylene glycol:ethanol=1:9, reaction temperature 160°C, reaction time 5 hours).

[0023] Fig.11 This is the XRD pattern of the In-amorphous-3 catalyst synthesized in Example 3 (indium nitrate hydrate, ethylene glycol:ethanol=1:2, reaction temperature 180°C, reaction time 5 hours).

[0024] Fig.12 This is a HR-TEM image of the In-amorphous-4 catalyst synthesized in Example 4 (indium nitrate hydrate, ethylene glycol:ethanol=1:2, reaction temperature 160°C, reaction time 3 hours).

[0025] Fig.13This is the Faraday efficiency diagram of the electrocatalytic CO2 reduction product of the In-amorphous-5 catalyst synthesized in Example 5 (indium nitrate hydrate, glycerol:ethanol=1:2, reaction temperature 160°C, reaction time 5 hours).

[0026] Fig.14 This is the XRD pattern of the In-amorphous-6 catalyst synthesized in Example 6 (indium chloride, ethylene glycol:ethanol=1:2, reaction temperature 160°C, reaction time 5 hours). DETAILED DESCRIPTION

[0027] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention will be further described in detail in combination with the following comparative examples and embodiments. The present invention synthesizes a series of amorphous indium-based catalysts by regulating factors such as solvent type, solvent ratio, reaction temperature, reaction time, etc. with a simple experimental method, and characterizes and tests the electrocatalytic CO2 reduction performance. This embodiment is based on the technical scheme of the present invention, and provides a detailed implementation method and a specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0028] Comparative Example 1 is an In2O3 catalyst. 0.002 mol of indium nitrate hydrate (In(NO3)3·xH2O) was dissolved in 51 mL of anhydrous ethanol and stirred for about 1 hour until it was completely dissolved; the resulting solution was transferred to a 100 mL stainless steel autoclave lined with polytetrafluoroethylene and heated at 160°C for 5 hours; the catalyst obtained by the reaction was washed by centrifugation with anhydrous ethanol and water, and finally dried in an oven to obtain a powdered In2O3 catalyst.

[0029] Comparative Example 2 is an In(OH)3-Commercial catalyst, which can be purchased directly on a chemical procurement platform.

[0030] Example 1 is an In-amorphous-1 catalyst (indium nitrate hydrate, ethylene glycol: ethanol = 1:2, reaction temperature 160 ° C, reaction time 5 hours). 0.002 mol In(NO3)3·xH2O was dissolved in 34 mL of anhydrous ethanol and stirred for about 1 hour until it was completely dissolved; 17 mL of ethylene glycol was slowly added to the solution and continued to stir for about 1 hour until the solution was transparent; the resulting solution was transferred to a 100 mL stainless steel autoclave lined with polytetrafluoroethylene and heated at 160 ° C for 5 hours; the catalyst obtained by the reaction was centrifugally cleaned with anhydrous ethanol and water, and finally dried in an oven to obtain a powdered In-amorphous-1 catalyst.

[0031] Example 2 is an In-amorphous-2 catalyst (indium nitrate hydrate, ethylene glycol: ethanol = 1:9, reaction temperature 160 ° C, reaction time 5 hours). 0.002 mol In (NO3) 3·xH2O was dissolved in 45.9 mL of anhydrous ethanol and stirred for about 1 hour until it was completely dissolved; 5.1 mL of ethylene glycol was slowly added to the solution, and stirring was continued for about 1 hour until the solution was transparent; the resulting solution was transferred to a 100 mL stainless steel autoclave lined with polytetrafluoroethylene and heated at 160 ° C for 5 hours; the catalyst obtained by the reaction was centrifugally cleaned with anhydrous ethanol and water, and finally dried in an oven to obtain a powdered In-amorphous-2 catalyst.

[0032] Example 3 is an In-amorphous-3 catalyst (indium nitrate hydrate, ethylene glycol: ethanol = 1:2, reaction temperature 180 ° C, reaction time 5 hours). 0.002 mol In(NO3)3·xH2O was dissolved in 34 mL of anhydrous ethanol and stirred for about 1 hour until it was completely dissolved; 17 mL of ethylene glycol was slowly added to the solution and continued to stir for about 1 hour until the solution was transparent; the resulting solution was transferred to a 100 mL stainless steel autoclave lined with polytetrafluoroethylene and heated at 180 ° C for 5 hours; the catalyst obtained by the reaction was centrifugally cleaned with anhydrous ethanol and water, and finally dried in an oven to obtain a powdered In-amorphous-3 catalyst.

[0033] Example 4 is an In-amorphous-4 catalyst (indium nitrate hydrate, ethylene glycol: ethanol = 1:2, reaction temperature 160 ° C, reaction time 3 hours). 0.002 mol In (NO3) 3·xH2O was dissolved in 34 mL of anhydrous ethanol and stirred for about 1 hour until it was completely dissolved; 17 mL of ethylene glycol was slowly added to the solution, and stirring was continued for about 1 hour until the solution was transparent; the resulting solution was transferred to a 100 mL stainless steel autoclave lined with polytetrafluoroethylene and heated at 160 ° C for 3 hours; the catalyst obtained by the reaction was centrifugally cleaned with anhydrous ethanol and water, and finally dried in an oven to obtain a powdered In-amorphous-4 catalyst.

[0034] Example 5 is an In-amorphous-5 catalyst (indium nitrate hydrate, glycerol: ethanol = 1:2, reaction temperature 160 ° C, reaction time 5 hours). 0.002 mol In (NO3) 3·xH2O was dissolved in 34 mL of anhydrous ethanol and stirred for about 1 hour until it was completely dissolved; 17 mL of glycerol was slowly added to the solution and continued to stir for about 1 hour until the solution was transparent; the resulting solution was transferred to a 100 mL stainless steel autoclave lined with polytetrafluoroethylene and heated at 160 ° C for 5 hours; the catalyst obtained by the reaction was centrifugally cleaned with anhydrous ethanol and water, and finally dried in an oven to obtain a powdered In-amorphous-5 catalyst.

[0035] Example 6 is an In-amorphous-6 catalyst (indium chloride, ethylene glycol: ethanol = 1:2, reaction temperature 160 ° C, reaction time 5 hours). 0.002 mol InCl3 was dissolved in 34 mL of anhydrous ethanol and stirred for about 1 hour until it was completely dissolved; 17 mL of ethylene glycol was slowly added to the solution and continued to stir for about 1 hour until the solution was transparent; the resulting solution was transferred to a 100 mL stainless steel autoclave lined with polytetrafluoroethylene and heated at 160 ° C for 5 hours; the catalyst obtained by the reaction was centrifugally cleaned with anhydrous ethanol and water, and finally dried in an oven to obtain a powdered In-amorphous-6 catalyst.

[0036] Example 7 is an XRD test. The catalyst prepared by the present invention is subjected to an XRD test. Figure 1 As shown, the catalyst synthesized in the ethanol solvothermal system in Comparative Example 1 was confirmed to be In2O3. Fig.11 As shown, the catalyst of Example 3 In-amorphous-3 has no diffraction peaks and is confirmed to be an amorphous catalyst. Fig.14 As shown, the catalyst of Example 6 In-amorphous-6 also has no diffraction peak, which is confirmed to be an amorphous catalyst.

[0037] Example 8 is a SEM test. The catalyst prepared by the present invention was subjected to a SEM test. Figure 4 As shown, the morphology of the In-amorphous-1 catalyst of Example 1 is spherical particles with a size of about 100 nm in diameter.

[0038] Example 9 is an EDS test. The catalyst prepared by the present invention was subjected to an EDS test. Figure 5 As shown, the In-amorphous-1 catalyst of Example 1 contains In element and O element, and the In element and the O element are evenly distributed.

[0039] Example 10 is a HR-TEM test. The catalyst prepared by the present invention was subjected to HR-TEM test. Figure 6 As shown, the catalyst In-amorphous-1 of Example 1 has no obvious lattice fringes and is confirmed to be an amorphous catalyst. Fig.12 As shown, the catalyst of Example 4 In-amorphous-4 also has no obvious lattice fringes and is confirmed to be an amorphous catalyst.

[0040] Example 11 is an LSV test for electrocatalytic CO2 reduction. The catalyst prepared by the present invention was subjected to LSV test in 1M KOH electrolyte using a flow electrolytic cell, Hg / HgO reference electrode, and anion exchange membrane. Figure 7 As shown, within the same voltage range, compared with the reaction in an argon (Ar) atmosphere, the In-amorphous-1 catalyst of Example 1 can obtain a larger reaction current when reacting in a CO2 atmosphere, indicating that the In-amorphous-1 catalyst has electrocatalytic CO2 reduction activity.

[0041] Example 12 is a constant current test for electrocatalytic CO2 reduction. A flow electrolytic cell, Hg / HgO reference electrode, and anion exchange membrane were used to maintain a CO2 gas flow rate of 20 mL / min, and a constant current test was performed on the catalyst prepared by the present invention in a 1M KOH electrolyte. Figure 2 As shown, the In2O3 catalyst of Comparative Example 1 is at -200~-800mAcm -2 The Faradaic efficiency of formic acid production is greater than 90% within the current density range, at -200mAcm -2 At the current density of -1000mAcm, the Faradaic efficiency of formic acid production can reach 97.0%; however, when the current density reaches -1000mAcm -2 When , the hydrogen evolution reaction intensifies and the Faradaic efficiency of formic acid production decreases to 60.0%.

[0042] like Figure 3 As shown, the comparative example 2 In(OH)3-Commercial catalyst is at -200~-600mA cm -2 The Faradaic efficiency of formic acid production is greater than 90% within the current density range, at -600mAcm -2 At the current density of -1000mAcm, the Faradaic efficiency of formic acid production can reach 96.3%; however, when the current density reaches -1000mAcm -2 When , the hydrogen evolution reaction intensified and the Faradaic efficiency of formic acid production decreased to 58.1%.

[0043] like Figure 8 As shown, the catalyst of Example 1 In-amorphous-1 is -200~-1000mAcm -2The Faradaic efficiency of formic acid production is greater than 96% within the current density range, at -800 mA cm -2 The Faraday efficiency of formic acid production can reach 98.0% under the current density of -1200mAcm -2 When the reaction temperature is 200 °C, the Faradaic efficiency of formic acid production can still reach 93.5%, which is the best catalyst among amorphous indium-based catalysts, indicating that amorphous indium-based catalysts have good electrocatalytic CO2 reduction performance to produce formic acid.

[0044] like Fig.10 Example 2 In-amorphous-2 shown in -200~-1000mAcm -2 The Faradaic efficiency of formic acid production is greater than 95% within the current density range, at -200 mA cm -2 At the current density of -1200mAcm, the Faradaic efficiency of formic acid production can reach 98.2%. -2 When , the hydrogen evolution reaction intensified and the Faradaic efficiency of formic acid production decreased to 85.0%.

[0045] like Fig.13 Example 5 In-amorphous-5 shown in -200~-1000mAcm -2 The Faradaic efficiency of formic acid production is greater than 94% within the current density range, at -600 mA cm -2 At the current density of -1200mAcm, the Faradaic efficiency of formic acid production can reach 97.2%. -2 When , the hydrogen evolution reaction intensified and the Faradaic efficiency of formic acid production decreased to 56.9%.

[0046] Example 13 is a stability test of electrocatalytic CO2 reduction. Using a flow electrolytic cell, Hg / HgO reference electrode, and anion exchange membrane, the stability test of the catalyst prepared by the present invention was carried out in a 1M KOH electrolyte while maintaining the CO2 gas flow rate at 20 mL / min. Fig. 9 As shown, Example 1 In-amorphous-1 catalyst at -200mAcm -2 The Faradaic efficiency of formic acid production can still be maintained at about 90% after 100 hours of reaction at the current density, indicating that the amorphous indium-based catalyst has good stability.

[0047] The above-described embodiments are only representative implementations of the present invention, so that those skilled in the art can understand and use them. It should be particularly noted that all similar replacements and modifications are considered to be included in the present invention.

Claims

1. An amorphous indium-based catalyst for electrocatalytic reduction of carbon dioxide to produce formic acid and a preparation method thereof, characterized in that: The preparation steps are as follows: (1) Dissolve 0.002 mol of indium salt in a certain amount of anhydrous ethanol and stir for about 1 hour until it is completely dissolved; (2) slowly adding a certain amount of polyol to the solution and continuing stirring for about 1 hour until the solution becomes transparent; (3) The resulting solution was transferred to a 100 mL stainless steel autoclave lined with polytetrafluoroethylene and heated at high temperature for several hours; (4) The catalyst obtained by the reaction is washed by centrifugation or filtration with anhydrous ethanol and water, and finally dried in an oven to obtain a powdered amorphous indium-based catalyst.

2. The amorphous indium-based catalyst for producing formic acid by electrocatalytic reduction of carbon dioxide and a preparation method thereof according to claim 1, characterized in that: Indium salts include indium nitrate and its hydrate, indium chloride and its hydrate, and the like.

3. The amorphous indium-based catalyst for producing formic acid by electrocatalytic reduction of carbon dioxide and a preparation method thereof according to claim 1, characterized in that: The solvent ratio of polyol to anhydrous ethanol is 0<polyol:ethanol<1, and the total volume of the mixed solvent is 51mL.

4. The amorphous indium-based catalyst for producing formic acid by electrocatalytic reduction of carbon dioxide and a preparation method thereof according to claim 1, characterized in that: The polyols include ethylene glycol, 1,2-propylene glycol, propylene glycol, butanediol (1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol), butanetriol (1,2,3-butanetriol, 1,2,4-butanetriol), butanetetraol, and the like.

5. The amorphous indium-based catalyst for producing formic acid by electrocatalytic reduction of carbon dioxide and a preparation method thereof according to claim 1, characterized in that: The reaction temperature ranges from 100°C to 200°C.

6. The amorphous indium-based catalyst for producing formic acid by electrocatalytic reduction of carbon dioxide and the preparation method thereof according to claim 1, characterized in that: The reaction time ranges from 3 to 10 hours.

7. An amorphous indium-based catalyst prepared according to the preparation method according to any one of claims 1 to 6.